Vaccines for Emerging Viral Diseases - DeZure, Adam (The Vaccine Book, 2016)
Infectious diseases continue to plague mankind and evolve to keep pace with the efforts to control them. Sir William Osler captured the ongoing fear of infectious pathogens when he said, “Humanity has but three great enemies: fever, famine, and war; of these by far the greatest, by far the most terrible, is fever.” Despite the significant impact of antimicrobials and vaccines on public health, there has only been one major human pathogen eradicated—variola virus, the agent of smallpox. In its place have been a series of new and reemerging microbes responsible for isolated infections, regional outbreaks, and global pandemics. Bacterial, fungal, and parasitic pathogens have the capacity to cause widespread epidemics such as the “Black Death” caused by Yersinia pestis in 14th century Europe. However, bacteria, fungi, and parasites are less likely to cause widespread human pandemics at this point in history and are less amenable to vaccine strategies than viral diseases. Focusing on viruses, a catalog of newly discovered human pathogens from the beginning of the 20th century shows a predictable and nearly linear rate of new agents discovered over time. However, of the more than 100 virus families, only 22 have been associated with human infections, a number that seems to have plateaued. In the chapter we will concentrate on vaccines for emerging viral diseases.